(untitled) (Research, Society and Development, 2022)
The study presents a description, analysis and reflection on bullying in Spain. In recent years the media have dealt extensively with this issue, echoing the most striking cases. In parallel, multiple programs have been implemented to eradicate or reduce bullying in the classroom, and the approach has been fragmentary and epidermal in many cases. Bullying in schools continues to have a high incidence in Spanish schools. Relevant bibliography, quantitative data and a total of 20 interviews have been conducted for the research: students, parents and primary and secondary teachers; who have explained their experiences and experiences. The contributions of the authors and informants show different causes and motivations from those socially accepted. Conflicts between peer students have traditionally been embedded in classrooms; currently, certain programs are implemented which have a specific approach. It requires a comprehensive and deep treatment, reinventing the values and principles of the school and incorporating compassion in everyday life and in all subjects.